A meta-analysis on the potency of foot-and-mouth disease vaccines in different animal models - Jiao Jiao; Peng Wu (Scientific Reports, 2024)
Abstract Whether mice can be used as a foot-and-mouth disease (FMD) model has been debated for a long time. However, the major histocompatibility complex between pigs and mice is very different. In this study, the protective effects of FMD vaccines in different animal models were analyzed by a meta-analysis. The databases PubMed, China Knowledge Infrastructure, EMBASE, and Baidu Academic were searched. For this purpose, we evaluated evidence from 14 studies that included 869 animals with FMD vaccines. A random effects model was used to combine effects using Review Manager 5.4 software. A forest plot showed that the protective effects in pigs were statistically non-significant from those in mice [MH = 0.56, 90% CI (0.20, 1.53), P = 0.26]. The protective effects in pigs were also statistically non-significant from those in guinea pigs [MH = 0.67, 95% CI (0.37, 1.21), P = 0.18] and suckling mice [MH = 1.70, 95% CI (0.10, 28.08), P = 0.71]. Non-inferiority test could provide a hypothesis that the models (mice, suckling mice and guinea pigs) could replace pigs as FMDV vaccine models to test the protective effect of the vaccine. Strict standard procedures should be established to promote the assumption that mice and guinea pigs should replace pigs in vaccine evaluation.